Kmart Corporation : saving an American icon (B) - Brown, Jason (SAGE Knowledge. Cases., 2017)
Jim Adamson, the man responsible for turning around Burger King and Advantica Restaurants, the parent company of Dennys Restaurants, has a new challenge. He has been hired to save Kmart, who in recent years has failed to remain competitive with the likes of Target and Wal-Mart. Despite three CEOs in as many years, the downward trend has continued for the big-box retailer. Investors are counting on Adamson to find a way to convince the market that Kmart can recover.